NUMERICAL SIMULATION OF THE FORMATION OF HAILSTONES IN THE CLOUDS AT THE NATURAL DEVELOPMENT AND AT THE ACTIVE INFLUENCE WITH THE HELP OF CRYSTALLIZING REAGENT - Vitaly Alexandrovich Shapovalov (Наука. Инновации. Технологии, 2022)
Introduction: Many important aspects of microphysical processes in hail clouds are still poorly understood due to the complexity of theoretical analysis and experimental research. The interaction of thermodynamic and microphysical processes in powerful convective clouds, electrical processes, interaction of the reagent with the cloud environment is not sufficiently studied. The relevance of the study is due to the need to develop scientifically valid methods of active impact to hail clouds. Materials and methods of research: The paper used a three-dimensional model of powerful convective clouds with a detailed description of thermodynamic, microphysical and electrical processes. The solution of the model equations was performed by a finite-difference method according to an implicit scheme of second-order accuracy with respect to spatial coordinates and time. When specifying the fields of the thermodynamic parameters of the atmosphere at the initial time, aer-ological sounding data or three-dimensional data from the global prediction model GFS were used. Results of the research and their discussion: The results of numerical experiments on the interaction of physical processes in high-power convective clouds show that an important consequence of the deformation of the fields of the thermodynamic characteristics of a cloud under the influence of ascending flows is an increase in the time of finding hailstones (or their path) in an area in which thermodynamic and micro-physical conditions are favorable for their growth. A study was made of the change in the microstructural characteristics of the cloud from the concentration of artiicial crystals and from the place of their application when the hail cloud was seeded with a crystallizing reagent. It is received that in the ield of inluence the radar relectivity decreases due to the appearance of many crystals, because of the induced supercooled droplets caused by the artiicial crystallization. Conclusions: Numerical experiments have shown the important role of interaction of processes of various types in the formation of the microstructure of clouds, in particular, in the formation and growth of hail particles. The most effective from the point of view of using the crystallizing reagent to reduce the danger of the cloud is to introduce it into a limited area, found as a result of numerical experiments. The effect of the crystallizing reagent on the microstructural parameters of the cloud as a result of seeding is determined.